Y(u)=(u^-2+u^-3)(u^5-2u^2), y'=? My attempt: =(-2u^-3 + -3u^-4)(u^5 - 2u^2) + (5u^4-4u)(u^-2+u^-3) =(-2u^2-4u^-1 -3u + 6u^-2) + (5u^2 +5u-4u^-1-4u^-2) =3u^2 +2u -8u^-1+2u^-2 Where did it go wrong?
Follow Math Help Forum on Facebook and Google+
=(-2u^-3 + -3u^-4)(u^5 - 2u^2) + (5u^4-4u)(u^-2+u^-3) =(-2u^2 + 4u^-1 -3u + 6u^-2) + (5u^2 +5u-4u^-1-4u^-2) the u^-1 terms cancel
****EDIT: Damn, you beat me to it Originally Posted by hazecraze Y(u)=(u^-2+u^-3)(u^5-2u^2), y'=? My attempt: =(-2u^-3 + -3u^-4)(u^5 - 2u^2) + (5u^4-4u)(u^-2+u^-3) =(-2u^2+4u^-1 -3u + 6u^-2) + (5u^2 +5u-4u^-1-4u^-2) =3u^2 +2u -8u^-1+2u^-2 Where did it go wrong? Try multiplying the brackets together before you take the derivative. It will be much easier.
View Tag Cloud